Expression of PRDX6 Correlates with Migration and Invasiveness of Colorectal Cancer Cells - Wen-Shih Huang; Cheng-Yi Huang; Meng-Chiao Hsieh; Yi-Hung Kuo; Shui-Yi Tung; Chien-Heng Shen; Yung-Yu Hsieh; Chih-Chuan Teng; Ko-Chao Lee; Kam-Fai Lee; Hsing-Chun Kuo (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Colorectal cancer (CRC) is the third most common type of cancer and the second leading cause of cancer-related deaths worldwide. PRDXs are antioxidant enzymes that play an important role in cell differentiation, proliferation and apoptosis and have diverse functions in malignancy development. However, the mechanism of aberrant overexpression of PRDX6 in CRC remains unclear. Methods: Boyden chamber assay, flow cytometry and a lentiviral shRNA targeting PRDX6 and transient transfection with pCMV-6-PRDX6 plasmid were used to examine the role of PRDX6 in the proliferation capacity and invasiveness of CRC cells. Immunohistochemistry (IHC) with tissue array containing 40 paraffin- embedded CRC tissue specimens and Western blot assays were used to detect target proteins. Results: PRDX6 was significantly up-expressed in different comparisons of metastasis of colorectal adenomas in node-positive CRC (P = 0.03). In in vitro HCT-116, PRDX6 silencing markedly suppressed CRC cell migration and invasiveness while also inducing cell cycle arrest as well as the generation of reactive oxygen species (ROS); specific overexpression of PRDX6 had the opposite effect. Mechanistically, the PRDX6 inactivation displayed decreased levels of PRDX6, N-cadherin, β-catenin, Vimentin, Slug, Snail and Twist-1 through the activation of the PI3K/ AKT/p38/p50 pathways, but they were also significantly inhibited by PRDX6 transfectants. There was also increased transcriptional activation of dimethylation of histone H3 lysine 4 (H3K4me3) of PRDX6 promoter via the activation of the PI3K/Akt/NFkB pathways. Conclusion: Our findings demonstrated that PRDX6 expression plays a characteristic growth-promoting role in CRC metastasis. This study suggests that PRDX6 may serve as a biomarker of node-positive status and may have a role as an important endogenous regulator of cancer cell tumorigenicity in CRC. PRDX6 may also be an effective therapeutic target.